‘Maqashid Al-Sharia’ Perspective for Character Building among Street Children in Makassar, South Sulawesi. - Ipandang Ipandang (Al-Ulum, 2015)
Negative images to street children have raised attention for all those concerned about the street children’s character building. This article discusses three basic problems; the street children reality in Makassar city, fostering and emergence of factors of street children and ‘maqashid al-sharia’ principles on character building for the street children in Makassar, South Sulawesi. In the perspective of ‘maqashid al-sharia’, the position of street children clearly has rules and normative legal basis. Fostering children's character has a fundamental meaning which is the basis of values to change the fate of children, as well as a comprehensive approach to man in spiritual education and noble character. This article meant to emphasize the role of ‘maqashid al-sharia’ perspectives in character building; therefore, street children of Makassar will struggle toward a better future.